The epic tradition of Pudoga - Novikov, Y. (Literatūra, 1974)
The article deals with the epic tradition of Pudoga – one of the most significant regions where the Russian popular epic poetry is current. The author’s attention focuses on the texts of byliny, which had been recorded here during the last century. The comparison of these records with the ones from the neighbouring regions shows that the epic repertoire of Pudoga is highly original and it contains a number of rare song plots. Local singers elaborated peculiar versions and wordings of many song plots and original diction, moreover, there are not a few archaic motifs and minutiae in their texts. During the last century borrowings and adoptions from the epic repertoires of neighbouring regions were rare, local tradition prevailed over the neighbours’ influence. In view of these circumstances the author supposes that the epic tradition of Pudoga is rather archaic and original and that the current belief in its recent rise stands in need of revision.